Influence of the composition of composite mixtures with a reduced gluten content on the rheological properties of the dough based on their basis - Ju. V. Ushakova; E. M. Paskova; G. E. Rysmukhambetova; T. B. Kulevatova (Новые технологии, 2020)
The article presents experimental data on the assessment of the rheological properties of dough from new types of flour, formed on the basis of cumulative curves using the Mixolab device. The data of mixolabograms and radial diagrams (Mixolab profiler) made it possible to reveal the existing differences in the parameters of the rheological profile and Mixolab indices. The object of the study is composite mixtures of gluten-free flours: No. 1 is 50% of pumpkin and 50% of corn flour, No. 2 is 50% of linseed and 50% of corn flour, No. 3 – 50% of rice and 50% of corn flour, No. 4 – 75% of linseed and 25% of corn flour, No. 5 is 30% of linseed and 70% of rice flour. The use of composite mixtures is promising due to high oven rise and low starch thickening because of its high water absorption capacity (WAC). In addition, there is certain economic efficiency, since it is possible to produce more dough at a lower cost.